2013
DOI: 10.1108/02634501311292902
|View full text |Cite
|
Sign up to set email alerts
|

The effect of environmental concern and scepticism on green purchase behaviour

Abstract: Purpose -The aims of the study are: to compare the environmental concern and scepticism levels of the participants and whether or not they display green purchase behaviour; to investigate the influence of environmental concern and scepticism on green purchase behaviour by utilizing the Theory of Planned Behaviour. Design/methodology/approach -The data were collected from participant and non-participant customers of the e-invoicing program of Turk Telecom. Customers were clustered into four groups according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
203
2
21

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 286 publications
(239 citation statements)
references
References 26 publications
13
203
2
21
Order By: Relevance
“…This means that as the environmental concerns of the consumer increase, green purchasing decision will also increase. Biswas and Mousumi (2015), Bertrandias and Gambier (2014), Albayrak et al (2013) were among the researchers who found similar results. They believed that the environmental concerns affect purchasing intention directly.…”
Section: Conclusion and Recommendationssupporting
confidence: 64%
See 3 more Smart Citations
“…This means that as the environmental concerns of the consumer increase, green purchasing decision will also increase. Biswas and Mousumi (2015), Bertrandias and Gambier (2014), Albayrak et al (2013) were among the researchers who found similar results. They believed that the environmental concerns affect purchasing intention directly.…”
Section: Conclusion and Recommendationssupporting
confidence: 64%
“…In fact, we conclude that as the attitude towards the environment increases, environmental concerns also increase. Investigating the results of Albayrak et al (2013), Singh and Bansal (2012) indicated that the customers who had higher levels of environmental concern and less doubts, reflected positive attitude and displayed more behavioral control and, therefore, had more motivation to purchase green products. According to the results of this research, it is recommended for marketers to focus on products that are compatible with the environment in their advertisement, because consumers welcome purchasing such products.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, environmental concern is often cited as a strong motivator to purchase [85,86]. Several studies have examined the influence of environmental concern on the green products purchase intention [84,87,88]. Irawan and Darmayanti [88] also reported a positive impact of the environmental concern on green purchase intention among university students in Indonesia.…”
Section: Environmental Concern (Ec)mentioning
confidence: 97%